L’opération «Liberté pour l’Irak» et ses conséquences sur la sécurité et la stabilité régionales - Kefala, Paraskevi (Études helléniques / Hellenic Studies, 2006)
After three years of war, Iraq has not managed to rebuild economically or socio-politically; instead, it has fallen into an entrenched civil war. The situation raises the issue of the very existence of an Iraqi state as well as its non-religious status. It also represents a threat to regional security and stability, both seriously affected since September 11.